ECONOMIC MANAGEMENT MECHANISMS IN THE ROSTOV REGION: ANALITICAL ASPECT - Kirill K. Krivonos (Статистика и экономика, 2016)
The article describes and discovers new mechanisms of regional economic management system in the Rostov Region, their similarities and differences, as well as its impact on the economy of the region and its participants. Provided data and current situation in socio-economic sphere analysis scheme became basis for regional development strategy and define areas which are need for one or another regional economics management mechanism to be applied.